Service crops improve a degraded monoculture system by changing common bean rhizospheric soil microbiota and reducing soil-borne fungal diseases - Aban, Carla Luciana; Verdenelli, Romina Aylén; Vargas Gil, Silvina; Huidobro, Dina Jorgelina; Meriles, José Manuel; Perez Brandan, Carolina (Oxford University Press, 2024)
Intensive agricultural practices have resulted in progressive soil degradation, with consequences on soil ecosystem services. The inclusion of service crops is a promising alternative to support the sustainability of the agricultural system. The aim of this study was to analyze in a six-year field experiment the effect of Brachiaria brizantha (perennial tropical grass) and Zea mays as service crops in a degraded common bean monoculture system in northwest Argentina. After six years, service crop treatments revealed a significant increase in most physical, chemical and biological properties of the soil (enzyme activities, microbial biomass, respiration and glomalin-related soil protein), compared with common bean monoculture. Also, a lower disease incidence was observed under B. brizantha treatments, associated with increased populations of Trichoderma spp. and Gliocladium spp. The phospholipid fatty acid profiles detected higher values of total microbial biomass under service crops. Our results suggest that the inclusion of several cycles of B. brizantha constitutes a promising soil management for recovering degraded agroecosystems.